Meaning and Symbols of Prabu Siliwangi Meditate and Purify Oneself: Folklore Study - Yan Nurcahya; Deri Sugiarto; M Kautsar Thariq Syah (Jomantara Indonesian Journal of Art and Culture, 2025)
Abstract: Folklore is a discipline, which stands alone in Indonesia, which has not been developed for long. Folklore is part of a collective culture, which is spread and passed down from generation to generation. To be able to distinguish it from culture. History is an empirical science. The consequence is that every historical statement must be based on a reliable source (fact). There is no historical source, no historical source then there is no history. This is what distinguishes history from fairy tales. Storytelling is a product of fictional imagination. In fairy tales, there is no claim that the story is told based on empirical facts or not, whether it really happened or not. Through Patilasan Dipatiukur and Prabu Siliwangi we can reflect on the struggle and courage that shaped the history of this nation. The traces of Dipatiukur and Prabu Siliwangi carved in every stone and puddle of water in this place remind us of the importance of respecting and studying valuable historical heritage. Keywords: Pajajaran Kingdom, Spread of Religion, Islam, Sundanese History